2015
DOI: 10.1111/acer.12775
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Developmental Alcohol Exposure on Potentiation and Depression of Visual Cortex Responses

Abstract: Background Neuronal plasticity deficits are thought to underlie abnormal neurodevelopment in Fetal Alcohol Spectrum Disorders (FASD) and in animal models of this condition. Previously, we found that alcohol exposure during a period that is similar to the last months of gestation in humans disrupts ocular dominance plasticity (ODP), as measured in superficial cortical layers. We hypothesize that exposure to alcohol can differentially affect the potentiation and depression of responses that are necessary for act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 51 publications
2
13
0
Order By: Relevance
“…2). Agreeing with prior literature, we found that without deprivation, EtOH mice had a contralateral eye bias no different from that of either SEP or SAL controls (Lantz et al, 2015). After 4 days of contralateral eye monocular deprivation, BGS EtOH treated mice exhibited ODIs that were not significantly different from those in the ND EtOH group, demonstrating that the ocular dominance shift toward the open eye did not occur properly.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…2). Agreeing with prior literature, we found that without deprivation, EtOH mice had a contralateral eye bias no different from that of either SEP or SAL controls (Lantz et al, 2015). After 4 days of contralateral eye monocular deprivation, BGS EtOH treated mice exhibited ODIs that were not significantly different from those in the ND EtOH group, demonstrating that the ocular dominance shift toward the open eye did not occur properly.…”
Section: Discussionsupporting
confidence: 89%
“…We focused on assessing microglial phenotype in the visual cortex, a brain region showing deficits in experience-dependent synaptic plasticity in early adolescent mice following our model of BGS EtOH exposure (Fig. 2, (Lantz et al, 2015)). Because recent studies have implicated microglia as critical players in experience-dependent plasticity, we hypothesized that BGS EtOH might alter the physiological phenotype of microglia in a way that would impair synaptic plasticity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations